Neural Population Dynamics Underlying Motor Learning Transfer - Vyas, Saurabh; Even-Chen, Nir; Stavisky, Sergey D.; Ryu, Stephen I.; Nuyujukian, Paul; Shenoy, Krishna V. (Neuron (Cambridge, Mass.), 2018)
Covert motor learning can sometimes transfer to overt behavior. We investigated the neural mechanism underlying transfer by constructing a two-context paradigm. Subjects performed cursor movements either overtly using arm movements, or covertly via a brain-machine interface that moves the cursor based on motor cortical activity (in lieu of arm movement). These tasks helped evaluate whether and how cortical changes resulting from “covert rehearsal” affect overt performance. We found that covert learning indeed transfers to overt performance and is accompanied by systematic population-level changes in motor preparatory activity. Current models of motor cortical function ascribe motor preparation to achieving initial conditions favorable for subsequent movement-period neural dynamics. We found that covert and overt contexts share these initial conditions, and covert rehearsal manipulates them in a manner that persists across context changes, thus facilitating overt motor learning. This transfer learning mechanism might provide new insights into other covert processes like mental rehearsal. •Covert learning via a brain-machine interface transfers to overt reaching behavior•Covert learning systematically changes motor cortical preparatory activity•Covert and overt movements share preparatory neural states and facilitate transfer•Covert and overt movements engage a similar neural dynamical system Vyas et al. ask whether learning “covertly,” without physical movements, can transfer to overt behavior. By using visuomotor perturbations, they show that covert and overt movements derive from a common neural substrate consisting of motor cortical preparatory activity that facilitates transfer of learning.